2013
DOI: 10.1159/000354432
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Flow Cytometry in Thyroid Cytopathology

Abstract: Background: Fine-needle aspiration (FNA) is a useful diagnostic tool for preoperative evaluation of thyroid nodules. However, cytomorphology alone has poor accuracy for the diagnosis of lymphoproliferative disorders involving the thyroid. This study reviews our experience with flow cytometry on thyroid FNA and correlation with surgical follow-up at The Johns Hopkins Hospital. Methods: The 11,118 thyroid FNAs performed over a 20-year period were reviewed for clinical flow cytometry data (n = 62) or a subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Clinical and US data of these 2 cases were consistent with the FC and/or the FNC diagnoses of TL and the histological examinations confirmed the TL diagnoses. Therefore, we think that the report of 2 ‘clonal', non-lymphomatous HT cases in the series of Boonyaarunnate et al [1] may further confirm the possible occurrence of small B-cell populations with light chain restriction in a variable number of HT cases. We would also like to stress the risk of overevaluating their meaning, especially in the absence of any clinical and US evidence of TL, and in our opinion the data of Boonyaarunnate et al [1] may support these data, too.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Clinical and US data of these 2 cases were consistent with the FC and/or the FNC diagnoses of TL and the histological examinations confirmed the TL diagnoses. Therefore, we think that the report of 2 ‘clonal', non-lymphomatous HT cases in the series of Boonyaarunnate et al [1] may further confirm the possible occurrence of small B-cell populations with light chain restriction in a variable number of HT cases. We would also like to stress the risk of overevaluating their meaning, especially in the absence of any clinical and US evidence of TL, and in our opinion the data of Boonyaarunnate et al [1] may support these data, too.…”
mentioning
confidence: 74%
“…We read with great interest the article ‘Impact of flow cytometry in thyroid cytopathology' by Boonyaarunnate et al [1] published in the last November-December issue of Acta Cytologica . In this study, the authors investigated 13 cases of primary thyroid non-Hodgkin lymphoma (TL) and 33 cases of Hashimoto thyroiditis (HT) by fine needle cytology (FNC) and flow cytometry (FC).…”
mentioning
confidence: 99%
“…1 The annual incidence of primary thyroid lymphoma (PTL) has been reported to be 1 to 2 cases per million. 2 Most thyroid lymphomas are nonHodgkin B-cell lymphomas, such as diffuse large B-cell lymphoma (DLBCL) and extranodal marginal zone lymphoma (ENMZL).…”
Section: Discussionmentioning
confidence: 99%
“…The literature that we are aware of that reports the use of FC is listed in table 2[29,30,31,32,33,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. Two papers were case reports [48,54]; some included thyroid specimens in studies performed to assess the overall value of FNA in NHL diagnosis [29,30,32].…”
Section: Thyroid Lymphoproliferative Processesmentioning
confidence: 99%
“…Two papers were case reports [48,54]; some included thyroid specimens in studies performed to assess the overall value of FNA in NHL diagnosis [29,30,32]. Among the studies carried out to evaluate the role of cytology in the differential diagnosis of thyroid lymphoproliferative processes, only three reports focused on the role played by FC [42,56,57]. Our study [42] and the work by Boonyaarunnate et al [56] reported the highest number of lymphomas identified, both concluding that the combined use of FNA-FC plays a fundamental role in the identification of this rare form of extranodal lymphoma.…”
Section: Thyroid Lymphoproliferative Processesmentioning
confidence: 99%